PERANCANGAN SISTEM INFORMASI ABSENSI KEHADIRAN SISWA BERBASIS WEB PADA SMK MUHAMMADIYAH 3 KLATEN UTARA - Nurma Yuliana; Agustinus Suradi; Syams Kurniawan Hidayat; Hendro Joko Prasetyo (Journal of Computer Science and Technology, 2022)
SMK Muhammadiyah 3 Klaten Utara is one of the private schools whose attendance media still uses an attendance manual or handwriting. By using handwritten attendance media, sometimes the stored data is damaged and easily lost so that attendance recapitulation takes a long time. The lack of communication and information between the school and parents resulted in students being able to report that they were in learning activities but in fact the students were playing with friends. So we need a web-based information system that is connected to a network using an SMS Gateway that can be directly connected to parents to control their children going to school or not. Web-Based Student Attendance Attendance Information System Design at Smk Muhammadiyah 3 Klaten Utara aims to help solve these problems. This information system will be able to manage student data, department data, class data, user data, input attendance data, sms and reports that can recapitulate attendance data. The method in designing this information system uses the waterfall model, using the method of observation and interviews at the time the research was conducted. Applications designed and designed using the Unified Modeling Language (UML), and built using a web-based application using the PHP (Hypertext Preprocessor) programming language, and also equipped with a database designed using MySQL and Modem and Gammu as a tool for sending messages. With this application, you can find out the activities of students who are present at school